Levels of basic competencies of the BRAC school graduates of 1995 and 1997 - Nath, Samir Ranjan; Imam, Syeda Rumnaz; Chowdhury, A Mushtaque R. (BRAC Research and Evaluation Division (RED), 2020)
The education programme of BRAC is designed to provide quality basic education to the poor children of Bangladesh. Based on the Declaration of the World Conference on Education, BRAC designed an instrument to measure the level of basic education of Bangladeshi children. The Research and Evaluation Division of BRAC regularly monitors the performance of graduates of BRAC schools through this instrument. This report presents the basic educational and enrolment status qf the graduates of two cohorts of 1995 and 1997. Two independent samples were drawn from two cohorts and the learners were tested nine/ten months after their graduation. The sample from 1995 cohort was also tested in 1997. Children from three systems of BRAC schools were assessed: those in Non Formal Primary Education (NFPE) and in Basic Education for Older Children (BEOC) which was directly operated by BRAC, and NFPE under the Education Support Programme (ESP) whom are operated by other NGOs using the BRAC model. The sample sizes for the two independent surveys were J259 each. Among the 1259 graduates of 1995, 949 could be traced in 1997 (75%).